Legal aspects of solid waste recycling and disposal in Kazakhstan: international standards and national regulation in the context of a circular economy - Nukusheva, A.A.; Assanova, S.E. (Bulletin of the Karaganda University “Law Series”, 2024)
The Republic of Kazakhstan, possessing significant natural resources and a rapidly developing economy, is faced with growing volumes of municipal solid waste (MSW), which requires effective measures for their processing and disposal. The main purpose of this study is to analyze the legal aspects of solid waste management in Kazakhstan, assess the compliance of national legislation with international standards and explore the potential for integrating the principles of a circular economy. The study covers the current state of the legal regulation of solid household waste in Kazakhstan and identifies key problems. The use of methods of political and legal analysis, comparative legal approach and system analysis helps to assess how modern initiatives can contribute to improving solid waste management and maintaining environmental balance. The conclusions of the study indicate the need to improve the legislative framework of Kazakhstan for the management of solid household waste. The introduction of a new Ecological Code based on the European principles of waste management hierarchy and extended producer responsibility is an important step forward. However, further progress requires the adoption of the Law “On Waste”, which would specify the implementation of the principles of the circular economy. The importance of creating conditions for small and medium-sized businesses in the field of waste recycling and increasing environmental awareness of the population through informing and involving public organizations and the media is also emphasized.